2017
DOI: 10.1039/c7ee02537h
|View full text |Cite
|
Sign up to set email alerts
|

Highly active, stable oxidized platinum clusters as electrocatalysts for the hydrogen evolution reaction

Abstract: Oxidized Pt clusters on a TiO2support as a robust electrocatalyst for the hydrogen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
177
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 275 publications
(196 citation statements)
references
References 54 publications
19
177
0
Order By: Relevance
“…To further investigate the coordination structure of Pt species in the heterostructure,t he Pt L 3 -edge X-ray absorption near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectra were investigated. As shown in Figure 2e,the white line (WL) intensity reflects the oxidation state of Pt species.I ti sc lear that the WL intensities increase in the order of Pt foil < Pt NPs < Pt/ Ni(HCO 3 ) 2 ,i ndicating that Pt in the heterostructure carries more positive charges and electrons transfer from Pt to Ni(HCO 3 ) 2 , [23] which is in accordance with XPS analysis (Figure 2b-d). Figure 2f exhibits the Fourier transforms of the Pt L 3 -edge EXAFS oscillations.T he main peak at 2-3 arises from PtÀPt bonding,a nd the relative intensity of Pt/ Ni(HCO 3 ) 2 is extremely weaker than that of Pt NPs,revealing weaker Pt À Pt coordination in the heterostructure.…”
supporting
confidence: 80%
“…To further investigate the coordination structure of Pt species in the heterostructure,t he Pt L 3 -edge X-ray absorption near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectra were investigated. As shown in Figure 2e,the white line (WL) intensity reflects the oxidation state of Pt species.I ti sc lear that the WL intensities increase in the order of Pt foil < Pt NPs < Pt/ Ni(HCO 3 ) 2 ,i ndicating that Pt in the heterostructure carries more positive charges and electrons transfer from Pt to Ni(HCO 3 ) 2 , [23] which is in accordance with XPS analysis (Figure 2b-d). Figure 2f exhibits the Fourier transforms of the Pt L 3 -edge EXAFS oscillations.T he main peak at 2-3 arises from PtÀPt bonding,a nd the relative intensity of Pt/ Ni(HCO 3 ) 2 is extremely weaker than that of Pt NPs,revealing weaker Pt À Pt coordination in the heterostructure.…”
supporting
confidence: 80%
“…The reason has not been clearly clarified so far. Recently, great efforts have been made to prepare platinum oxide models such as PtO x /TiO 2 24 and MoS x -O-PtO x 25 and confirmed that the presence of oxygen in Pt catalysts did possess superior HER catalytic performance comparable to that of commercial Pt/C and even superior to that of MoS x -Pt. These pioneering works inspired chemists to find more suitable and distinct platinum oxide models so as to reveal the role of oxygen in Pt-based electrocatalysts and develop new efficient electrocatalysts superior to commercial Pt/C.…”
mentioning
confidence: 98%
“…Figure 4dcompares with the overpotential at 10 mA cm -2 current density and the corresponding Tafel slope of various MoS2-based and TiO2-based electrocatalysts[16][17][18][19][20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%